Coupling solid-phase microextractions and surface-enhanced Raman scattering: towards a point-of-need tool for hepatic cancer screening. Issue 32 (9th August 2017) - Granger, Jennifer H.; Skuratovsky, Aleksander; Porter, Marc D.; Scaife, Courtney L.; Shea, Jill E.; Li, Qun; Wang, Sean
Abstract : A method for rapid, highly portable immunoassays at low limits of detection has been developed by combining solid-phase microextraction membranes, gold nanoparticle labels, and surface-enhanced Raman scattering. Abstract : A method for performing rapid, highly portable immunoassays at low limits of detection (LoD) has been developed by combining solid-phase microextraction membranes, gold nanoparticle labels, and surface-enhanced Raman scattering. The capability of this methodology is demonstrated through measurements of alphafetoprotein, a marker used to screen individuals for hepatocellular carcinoma, directly from human serum at an estimated LoD of 3 pg mL −1 in ∼2 min.